TRANSFORMASI PENDIDIKAN UNTUK MENGATASI KONFLIK MASYARAKAT DALAM PERSPEKTIF MULTIKULTURAL - Aidil Sudarmono (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2019)
Globalization is a process that integrates series of global life. The link between globalization and education will have new society namely a society based on "knowledge-based-society". For that reason, education is vital in realizingn a future society based on science, because the process of transformation through education and scientific development will occur. Transformation of education in multicultural perspective should facilitate teaching and learning process that change essential mono-cultural essential perspective, which is full of prejudice, and discriminative to the multicultural perspective which respect differences, tolerance, and open mindedness.Transformation of education should also be able to provide the partly designing the materials, methods, curriculum that enable people enlightening idea, tobe aware of the importance of mutual tolerance, respect for differences in inethnicity, religion, race, ethnicity and culture of Indonesia's multicultural society